Взаємозв’язок між фізичною та технічною підготовленістю юних борців - Кедровський, Борис; Шалар, Олег; Іздебський, Івана; Kedrovskyi, Borys; Shalar, Oleh; Izdebskyi, Ivan (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Мета статті – визначення змісту фізичної та технічної підготовки юних борців; виявлення та обґрунтування взаємозв’язку між їхньою фізичною й технічною підготовленістю. У дослідженні брало участь 20 борців-новачків 11–14 років. Усіх спортсменів поділено на дві групи. До першої увійшли борці 13–14 років, які навчаються в ДЮСШ № 3, а до другої – 11–12 років, учні ДЮСШ «Спартак» м. Херсона. Показано рівні фізичної та технічної підготовленості юних борців. Із тесту «переворотом з упору головою в килим й у зворотному напрямку» в першій групі високого рівня досягли всі борці, а в другій – 80 %. За показниками гнучкості 80 % юних борців першої групы мали високий рівень, а в другій групі ‒ відповідно, 70 %. Під час змагань кількість борців із високим рівнем техніко-тактичної підготовленості зріс на 10 % у першій групі, тоді як у другій – навпаки, зменшився на 40 %. Установлено досить високий коефіцієнт кореляції в другій групі між гнучкістю й показником швидкісно-силового характеру (забігання навколо голови) та гнучкістю й показником спеціальної спритності борця (перекиди з упору головою в килим), який дорівнює (r = 0,7) в обох випадках. Отже, у сфері підготовки юних борців має втілюватися методика оптимального співвідношення фізичних і технічних вправ на підготовчому етапі спортивного тренування. Objective: defining of physical and technical training of young wrestlers; revealing and grounding of interrelation of their physical and technical preparedness. Material: the study involved 20 wrestlers–beginners aged 11–14. All athletes were divided into two groups. The first group consisted of wrestlers aged 13–14 enrolled in the sports school № 3, and the second one was 11–12 years old pupils of sports school «Spartak», Kherson. Results: the results showed the levels of physical and technical preparedness of young wrestlers. On the test «by the coup from the stop head in the carpet and in the opposite direction» in the first group reached a high level all wrestlers, and in the second group – 80 %. In terms of flexibility 80 % of young wrestlers of the first group had a high level, and in the second group ‒ 70 %, respectively. During the competition the number of wrestlers with a high level of technical and tactical training rose 10% in the first group, while the fighters of the second group, conversely, decreased by 40 %. Set a fairly high correlation coefficient in the second group between flexibility and indicator speed-power character (running around the head), and flexibility and indicator special agility of a wrestler (somersaults from the stop head in the carpet) that is equal to (r = 0,7) in both cases. Conclusions: in the training of young wrestlers should be embodied method of the optimal ratio of physical and technical exercises in the preparatory stage of sports training.
Interrelation Between Physical and Technical Preparedness of Young Wrestlers
Keywords: юні борці; фізична підготовленість; технічна підготовленість; кореляція; спортивне тренування; young wrestlers; physical preparedness; technical preparedness; correlation; sports training